The Value of Human Resource Flexibility: A Study of Private and Public Organisations in The Gambia - Badjie, Gibriel (STIE Widya Manggala, 2020)
Human resource flexibility has attracted lots of research attention, but limited papers categorically address the benefits of HR flexibility to employees. This paper ispurposely crafted to address the knowledge gap and bridge the perception and expectation gap from both sides regarding the benefit of HR flexibility. The research uses a mixed method approach. First used questionnaire-based survey, but and second interviewed 10 employees randomly selected from organisations that participate in the survey. About 80 senior HR personnel participated in the survey representing the views of 40 private and public organisations. A stratified random sampling technique was used using two organisation directories as sample frame. The outcome of the study discovers differences in the practice of HR flexibility between private and public organisations in the Gambia. The outcome also dictates that, the views expressed by the senior HR personnel cannot represent the position of the employees. HR flexibility has economic and social benefits for the organisation and employees, therefore further study is recommended to delve deep into the issues.